CERAI GUGAT KARENA PENCURIAN DALAM RUMAH TANGGA: Studi Putusan Nomor 2223/Pdt.G/2020/PA.JS. - Qatrunnada Ananda Rafidah, (2022)
According to Article 114 of the Compilation of Islamic Law (KHI), dissolution of marriage can occur because of repudiation divorce or judicial divorce. Judicial divorce filed by the wife or her attorney at the Religious Court is an important focus of research. Analysis of how the judge considers if the husband commits theft in the household and also to whom the custody of children under the age of 12 is assigned. The study of the judicial divorce case for divorce in Decision Number 2223/Pdt.G/2020/PA.JS, which needed as a data for research that there are reasons for divorce based on theft in the household. This research is a normative-empirical research, which means literature study by researching library materials and researching with support from the results of interviews. The results of the study stated that the judge's considerations were not focused on the theft committed by the husband against the innate property owned by the wife. The judge's consideration requires the Defendant (husband) to continue to raise the child while the Defendant does not have the skills to hold child custody as explained in Article 116 letter g of the Compilation of Islamic Laws that the maintenance that is not paid by the husband for 3 months or more can result in a debt for the husband.